PEMANFAATAN APLIKASI EVERYCIRCUIT DAN LOGIC CIRCUIT SIMULATOR SEBAGAI LABORATORIUM VIRTUAL PADA PRAKTIKUM FISIKA POKOK BAHASAN KELISTRIKAN - Tatang Sutarman; Rahman Rahman; Khaeriah Dahlan; Wahyu Kumala Sari (LPPM Uncen, 2023)
This Floods occur frequently in Indonesai also in Jayapura, one of the negative impacts being felt on the world of education, namely the damage to educational facilities and infrastructure, including damage to the tools used to carry out physics practicums at SMA Negeri 4 Jayapura. Efforts to continue to carry out practicum activities are by utilizing applications found on smartphones as practicum media including the EveryCircuit application and Logic Circuit Simulator in electrical experiments. In carrying out the activity, no significant obstacles were found because the students were accustomed to using smartphones and easily understood the use of the given application because a practicum guidebook was available. The EveryCircuit application and Logic Circuit Simulator can be used as a tool to be used as a virtual laboratory in carrying out physics practicums in schools, especially in the learning process during the post-disaster period and for schools that do not yet have a laboratory or special equipment in the electronics field.Ã‚Â Keywords: the everycircuit application; logic circuit simulator; educational facilities and infrastructure; educationÃ‚Â